Tracking sound source localization for a home robot application - Lopes, Gil (2016)
The future of robotics is now trending for home servicing. Nursing homes and assistance to elder peopleare areas where robots can provide valuable help in order to improve the quality of life of those who need it most. Calling a robot,for a person of age,can be a daunting task if the voice is failing and any resort to battery operated devices failsto comply. Using a simple mechanical apparatus,such as aClick trainerfordogs, a person can call a robot by pressing thebutton of a powerless device. The high pitch sound produced by this device can be captured and tracked down in order to estimate the person’s location within a room. This paper describes a method that provides good accuracy and uses simple and low cost technology,in order to provide an efficient positional value for an assistance robot to attend its caller. The robot does not need to search for the person in aroom as it can directly travel towards the Click’s sound source.